Effects of PAX9 and MSX1 gene variants to hypodontia, tooth size and the type of congenitally missing teeth - GÜNEY, AHMET İLTER (C M B ASSOC, 2016)
Tooth agenesis, affecting up to 20% of human population, is one of the most common congenital disorder. The most frequent form of tooth agenesis is known as hypodontia, which is characterized by the absence of one to five permanent teeth excluding third molars. It was considered that hypodontia is especially related with gene mutations which play role in tooth formation. Additionally mutations in PAX9 and/or MSX1 have been identified as the defects responsible for missing permanent molars and second premolars. In some studies it was also found that PAX9 and MSX1 gene mutations may change tooth size. Therefore in this study all of these factors were investigated. Thirty one patients and 30 controls were enrolled to the study. Information about tooth sizes and type of congenitally missing teeth were collected. MSX1 and PAX9 gene mutations were investigated by direct sequencing. Results were evaluated statistically. As a result, 22 variations were detected in PAX9 in which 18 of them are novel. In addition, 7 variations were found in MSX1 in which 5 of them are novel and one of them lead to amino acid change. Statistically significant relations were found between detected variations and tooth sizes. Any relation between mutations and type of congenitally missing teeth were not detected. In conclusion, especially new mutations which may cause hypodontia, effect tooth size and type of congenitally missing teeth, should be investigated with other researchers for clarifying the mechanism.
Keywords: Hypodontia; PAX9; MSX1; tooth size; AUTOSOMAL-DOMINANT OLIGODONTIA; MISSENSE MUTATION; MOLAR OLIGODONTIA; NONSENSE MUTATION; DENTAL ANOMALIES; PAIRED DOMAIN; AGENESIS; IDENTIFICATION; FAMILY; MORPHOGENESIS